2022
DOI: 10.1108/bfj-07-2021-0798
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption and food waste behaviour in households in the context of the COVID-19 pandemic

Abstract: PurposeThis research aims to understand the behaviour of food consumption and waste in Peruvian households at the beginning of the COVID-19 pandemic.Design/methodology/approachExploratory research was carried out with Peruvian households, using a descriptive method design. Data were analysed using descriptive and multivariate statistics. A self-administered questionnaire of 60 questions was used, applied by social networks in May 2020, obtaining 418 valid questionnaires.FindingsThe main findings allow the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
(268 reference statements)
2
7
0
Order By: Relevance
“…Besides, similar to previous studies (Principato et al, 2021) our research sheds light on the complex sides of the food waste phenomenon, highlighting the trend of research on this topic (Zhang et al, 2018;Vásquez Neyra et al, 2022;D'Adamo et al, 2023). More specifically, our study provides an essential segment of information presenting the issues around food waste that are denoted as the motor themes with a critical role of food waste in future food waste management and policies, such as the concept of circular economy (de Oliveira et al, 2021;Nikolaou and Tsagarakis, 2021;Santagata et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…Besides, similar to previous studies (Principato et al, 2021) our research sheds light on the complex sides of the food waste phenomenon, highlighting the trend of research on this topic (Zhang et al, 2018;Vásquez Neyra et al, 2022;D'Adamo et al, 2023). More specifically, our study provides an essential segment of information presenting the issues around food waste that are denoted as the motor themes with a critical role of food waste in future food waste management and policies, such as the concept of circular economy (de Oliveira et al, 2021;Nikolaou and Tsagarakis, 2021;Santagata et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…For instance, Alfonso et al [15] have stated that plastic production, use, and waste generation in Latin America and the Caribbean has increased in the pandemic, resulting in more than half of this waste being non-recycled garbage, producing pollution in the oceans and on land. In the same vein, Neyra et al [47] have pointed out that food consumption and its direct waste generation (packaging) have increased during COVID-19. Another element is air pollution effects [7].…”
Section: Social Responsibility (Sr)mentioning
confidence: 97%
“…Burlea-Schiopoiu et al (2021) found that the COVID-19 pandemic changed the consumer behaviour of young people, who began to worry more about food waste, which could be taken as a general change in the behaviour of food consumers, who threw less food in the pandemic year, compared to earlier (WRAP, 2020). In general, the reduction of food wastage requires improving purchase planning, knowledge of labels, and food storage and cooking skills (V asquez Neyra et al, 2022). Indeed, Sharp et al (2021) found that lower levels of food waste were correlated with higher levels of cooking confidence.…”
Section: Household Food Wastagementioning
confidence: 99%